From ADDIE to CAMIL: A Systematic Review of Teaching Models for Enhancing Interactive Creativity Learning through Mobile Outcomes in Art Education - Zhao Yan; Jamilah binti Omar (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study aims to compare and analyze the effectiveness of the analysis-design-developmentimplementation-evaluation (ADDIE) and cognitive-emotional model for immersive learning (CAMIL) instructional design models in promoting the development of learners’ creativity in the field of art education through systematic literature review and meta-synthesis methods. Grounded in social constructivism and experiential learning theory (ELT), the analysis encompasses 25 peer-reviewed studies from Scopus, Web of Science, and ERIC published between 2019 and 2024. The results demonstrate that ADDIE facilitates structured instruction, skill development, and consistent assessment, yet provides limited adaptability for personalized and generative creativity. Conversely, CAMIL more effectively enhances learner autonomy, emotional engagement, and contextualized creative practice through its nonlinear, reflective design, though it requires greater teacher expertise and poses challenges in evaluating complex outcomes. Case studies further substantiate CAMIL’s advantages in fostering emotional and sociocultural creativity. The study recommends integrating the strengths of both models to establish a hybrid instructional approach that balances structure and flexibility in art education.